Clinical features and outcome of influenza pneumonia in critically-ill immunocompromised patients. Issue 49 (9th December 2022) - Raymond, Matthieu; Martin, Maëlle; Lamouche-Wilquin, Pauline; Blonz, Gauthier; Decamps, Paul; Agbakou, Maïté; Desmedt, Luc; Reignier, Jean; Lascarrou, Jean-Baptiste; Canet, Emmanuel
Abstract : Immunocompromised subjects are at risk of severe viral infections which may require intensive care unit (ICU) admission. Data on the outcome of influenza pneumonia in critically-ill immunocompromised subjects are limited. We conducted a single-center observational study. All subjects admitted to the ICU for influenza pneumonia between 2016 and 2020 were included. The main objective was to compare the clinical features and outcome of critically-ill subjects with flu according to their immune status. 137 subjects (age 60 years-old, 58.4% male) were included, of whom 58 (42.34%) were intubated during the ICU stay. Forty-three (31.4%) subjects were immunocompromised. Immunocompromised subjects had a higher Charlson comorbidity index. In contrast, severity scores and hypoxemia at ICU admission, and ventilatory support during ICU stay were similar between the 2 groups. There was no difference in the rate of co-infections and ventilator-associated pneumonia between the 2 groups. Among intubated subjects, 10 (23.26%) immunocompromised subjects developed severe acute respiratory distress syndrome compared to 13 (13.83%) non-immunocompromised ( P = .218). ICU mortality was 13.97%, with mortality being 3-times higher in immunocompromised subjects (25.58% vs 8.6%, P = .015). On multivariable analysis, immunocompromised status, higher age and lower arterial oxygen partial pressure/fraction of inspired oxygen were associated with an increased ICU mortality. Immunocompromised subjects with severe influenza pneumonia were more likely to develop severe acute respiratory distress syndrome and had a 3-fold increase in ICU mortality compared to non-immunocompromised subjects. Such difference was not explained by an increased rate of co-infections or nosocomial pneumonia, suggesting that influenza virus was by itself responsible of a more severe form of pulmonary disease in immunocompromised subjects.